Conductivity of nanoporous InP membranes investigated using terahertz spectroscopy. - Merchant, S; Lloyd-Hughes, J; Sirbu, L; Tiginyanu, I; Parkinson, P; Herz, L; Johnston, M (2008)
We have investigated the terahertz conductivity of extrinsic and photoexcited electrons in nanoporous indium phosphide (InP) at different pore densities and orientations. The form of electronic transport in the film was found to differ significantly from that for bulk InP. While photo-generated electrons showed Drude-like transport, the behaviour for extrinsic electrons deviated significantly from the Drude model. Time-resolved photoconductivity measurements found that carrier recombination was slow, with lifetimes exceeding 1 ns for all porosities and orientations. When considered together, these findings suggest that the surfaces created by the nanopores strongly alter the dynamics of both extrinsic and photoexcited electrons.